Electricity and magnetism - Kelly, P. F., 1961- (CRC Press, 2015)
List of ExamplesPrefaceElectricity and MagnetismElectric Charge, Coulomb's Law, Electric FieldElectric Dipole, Motion of Charged ParticlesContinuous Charge DistributionsAbove a Uniformly Charged Rectangular PlateElectric Flux and Gauss's LawMore Gauss's LawElectrostatic Implications and Potential EnergyPotentially Fun!Electrostatic Potential EnergyRife with PotentialPotentials, Fields, and All ThatCapacitanceCapacitors in Series and ParallelEnergetics of CapacitanceDielectricsEnergetics of DipolesElectric CurrentElectric Current Density, Ohm's Law, and ResistanceResistance Is Not FutileResisto.